2020
DOI: 10.2196/16341
|View full text |Cite
|
Sign up to set email alerts
|

Engagement and Clinical Improvement Among Older Adult Primary Care Patients Using a Mobile Intervention for Depression and Anxiety: Case Studies

Abstract: Background Technology-based mental health interventions are an increasingly attractive option for expanding access to mental health services within the primary care system. Older adults are among the groups that could potentially benefit from the growing ubiquity of technology-based mental health interventions; however, older adults are perceived to be averse to using technology and have reported barriers to use. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Interestingly, the only baseline factor associated with pattern of communication frequency was age; older participants were more likely to be in the first group (i.e., messaged coach more at the beginning and/or end of treatment). This is consistent with past literature suggesting that older users prefer—and may therefore benefit from— more human contact in digital therapies ( Orr et al, 2020 ; Wildenbos et al, 2019 ). Notably, we did not find that this was driven by technology or usability concerns.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the only baseline factor associated with pattern of communication frequency was age; older participants were more likely to be in the first group (i.e., messaged coach more at the beginning and/or end of treatment). This is consistent with past literature suggesting that older users prefer—and may therefore benefit from— more human contact in digital therapies ( Orr et al, 2020 ; Wildenbos et al, 2019 ). Notably, we did not find that this was driven by technology or usability concerns.…”
Section: Discussionsupporting
confidence: 92%
“…For example, quantity of coaching could be more important to older adults than to their younger counterparts. Studies have found that desire for human contact and technology literacy barriers can be deterrents for mental health app use, particularly among older adults; thus, more coaching may be beneficial for these users [ 55 , 109 ]. Moreover, others have found older adults to be more engaged with digital coaches than younger ones [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…Examining affective and cognitive engagement is crucial for developing a more thorough and nuanced understanding of the way people interact with apps. An idiographic approach was preferred to achieve a rich understanding of patterns of engagement [ 39 , 40 ] with this new app and as research on other apps has highlighted the heterogeneity in the preference of app features [ 26 ]. Exploring individual patterns of engagement with HabitWorks may inform further tailoring of the app to enhance its efficacy for high-risk populations, as well as inform the development of similar types of mental health apps.…”
Section: Introductionmentioning
confidence: 99%